Fine art photography as a form of visual art: Aesthetics, styles, and contemporary trends - Rochnyak, Andriy (Art and Design, 2025)
The study aimed to analyse fine art photography as a form of visual art, its aesthetic characteristics, stylistic evolution, and contemporary developmental trends. The research was based on the analysis of art-historical works, exhibition catalogues, artistic practices of leading photographers, as well as content analysis of digital platforms and the non-fungible token market. The study established that fine art photography has transcended its traditional documentary function and acquired the status of an autonomous conceptual medium, integrating elements of painting, cinematography, performance, and digital technologies. It was found that the stylistic transformations of fine art photography have been accompanied by experiments with form, light, composition, and narrative structure, particularly evident in the development of such movements as conceptual, staged, and minimalist photography. The results confirmed that fine art photography has evolved into a multidimensional artistic practice that combines visual aesthetics with conceptual content and actively interacts with other art forms. It was revealed that contemporary photographers not only experiment with genres and techniques but also shape new modes of audience engagement through digital platforms, the non-fungible token technologies, and social media. The study demonstrated that digital technologies open new possibilities for photographers, particularly in algorithmic editing, generative art, and the non-fungible token economy, while simultaneously transforming the methods of presentation and artist-audience interaction. The findings may be applied in art education, curatorial practice, and the development of new digital exhibition formats.